2023
DOI: 10.3389/fimmu.2023.1078736
|View full text |Cite
|
Sign up to set email alerts
|

Sex-disaggregated outcomes of adverse events after COVID-19 vaccination: A Dutch cohort study and review of the literature

Abstract: BackgroundAlbeit the need for sex-disaggregated results of adverse events after immunization (AEFIs) is gaining attention since the COVID-19 pandemic, studies with emphasis on sexual dimorphism in response to COVID-19 vaccination are relatively scarce. This prospective cohort study aimed to assess differences in the incidence and course of reported AEFIs after COVID-19 vaccination between males and females in the Netherlands and provides a summary of sex-disaggregated outcomes in published literature.MethodsPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 101 publications
3
8
0
Order By: Relevance
“…Notably, females demonstrated a heightened probability of encountering side effects with nearly double the likelihood compared to males for both local and systemic side effects. This aligns with findings from other studies ( 53 , 54 ). Clinical data highlights the impact of gender on the frequency and severity of vaccination-related adverse reactions, including fever, pain, and inflammation ( 55 ).…”
Section: Discussionsupporting
confidence: 93%
“…Notably, females demonstrated a heightened probability of encountering side effects with nearly double the likelihood compared to males for both local and systemic side effects. This aligns with findings from other studies ( 53 , 54 ). Clinical data highlights the impact of gender on the frequency and severity of vaccination-related adverse reactions, including fever, pain, and inflammation ( 55 ).…”
Section: Discussionsupporting
confidence: 93%
“…The current study revealed that most neurological AEFIs were more common in female with dyslipidemia, hypertension and diabetes mellitus in all three vaccine types, this finding is consistent with Dutch study which reported two-fold higher odds of having any AEFI as compared to males with most pronounced differences after the first dose and for nausea and injection site inflammation [10] . The most frequent clinical complaints of neurological AEFIs were numbness, headache and dizziness which are usually mild, short-duration, and self-limiting, similar to most studies [9] , [10] , [11] , [12] , [13] . Neurological AEFIs can be presented as the sole complaint or co-occurring with systemic AEFIs.…”
Section: Discussionsupporting
confidence: 92%
“…We demonstrated slightly higher overall AEFI reporting for females, particularly those aged 30–49 years of age. Sex disproportionality was expected in observed rates of injection site reaction, paresthesia, nausea and vomiting, consistent with pre-licensure studies[26, 27]. However, we also identified disproportional reporting in females for anaphylaxis, which has not been previously reported for Nuvaxovid, although a similar disproportionality had been noted by Somiya et .…”
Section: Discussionsupporting
confidence: 91%